Penerapan Keuangan Digital dalam Wakaf di Aplikasi Amalsholeh - Diska Amalia Sianti; Zainal Arif (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
In Islamic economics, there are several sectors that do not exist in conventional economics, namely voluntary sectors such as waqf. Waqf has played an important role in the social, economic, and cultural development of society. Now there are several digital-based applications that aim to make it easier for people to participate in waqf. Therefore, the author wants to examine how digital finance is applied in waqf in the Amalsholeh application. The main objective of this study is to identify digital finance-based cash waqf and understand its application in the Amalsholeh application. This study is a combination of literature research and descriptive research. Literature research is research in which the source data comes from books. Descriptive research is research that focuses on analysing a research object. The author also used previous research on waqf. Data collection techniques were carried out through observation, namely by observing the amalsholeh waqf application. The type of observation carried out was participant observation, whereby the author used the amalsholeh application. The author also used inductive techniques to identify data by drawing conclusions from various data. The steps in inductive research are data collection, data analysis, and then drawing conclusions from the findings. The result of this research is that waqf is a form of charity that is encouraged in Islam. Waqf is not only in the form of goods but can also be in the form of money. In Indonesia, digital waqf based on digital finance has emerged, making it easier for people to donate money online. There are many waqf applications, one of which is the Amalsholeh application, which has a waqf feature. Users of the Amalsholeh application can choose any waqf programme they want with various payment methods, and there is no minimum donation amount.